Mechanical properties of affordable and sustainable ultra-high-performance concrete. (June 2022) - Tahwia, Ahmed M.; Elgendy, Gamal M.; Amin, Mohamed
Abstract: The sustainability of UHPC necessitates and requires incorporating supplementary cementitious materials (SCMs) and eco-efficient materials. In this study, silica fume (SF), fly ash (FA), and granulated blast furnace slag (GBFS) were the utilized supplementary cementitious materials. Also, blast furnace cement (CEM III) was used as eco-efficient material. CEM III gains its sustainability benefits via containing about 36–65% granulated slag in its composition. This study aims to develop UHPC mixture proportions using SCMs and CEM III so that UHPC may be made more sustainable and affordable to a wider variety of applications. The largest possible part of the amount of Portland cement (PC) could be replaced with sustainable environmentally friendly materials. The main replacement material used in this study was blast furnace cement, where the type (CEM III/A) was used, which involves 50% granulated blast furnace slag (GBFS) in its combination. Thus, this cement is financially and environmentally sustainable. The PC was completely replaced by this sustainable cement in the majority of the mixtures of this study; and in other mixtures, a part of the PC weight was partially replaced by CEM III. On the other hand, FA and GBFS were also utilized as cement replacements from PC or CEM III main binder in the residual mixtures. Fifty-five different concrete mixes with SF contents of 15%, 20%, and 25%; and cement replacement percentages of 0%, 10%, 20%, 30%, 40%, and 50% were prepared with locally available materials. The mixes were tested for slump flow and mechanical properties. The findings of mechanical properties indicated that the optimum level for partial replacement of cement by CEM III, and GBFS was 10%, but for FA was 20%. The minimum 28 days compressive strength values of affordable and sustainable ultra-high-performance concrete were 160.9, 150.5, and 152.3 MPa which were detected at 50%, 30%, 20% replacement percentages of FA, CEM III, and GBFS respectively Highlights: The sustainability of UHPC using CEM III as the main binder was evaluated. Replacement of Portland cement with high percentages of SCMs in UHPC is investigated. Increasing replacement of CEM III would relatively improve workability of UHPC. Mechanical properties of UHPC are developed with FA cement replacement. Improved UHPC mechanical properties was emphasized by microstructure analysis.